2017
DOI: 10.1155/2017/4751780
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potent Chloride Intracellular Channel Protein 1 Inhibitors from Traditional Chinese Medicine through Structure-Based Virtual Screening and Molecular Dynamics Analysis

Abstract: Chloride intracellular channel 1 (CLIC1) is involved in the development of most aggressive human tumors, including gastric, colon, lung, liver, and glioblastoma cancers. It has become an attractive new therapeutic target for several types of cancer. In this work, we aim to identify natural products as potent CLIC1 inhibitors from Traditional Chinese Medicine (TCM) database using structure-based virtual screening and molecular dynamics (MD) simulation. First, structure-based docking was employed to screen the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…This is especially true if the studied drug has already proven good safety and tolerability profile in humans ( 76 ). Interestingly, a CLIC1 inhibitory activity was reported in some Chinese traditional medicine molecules, identified by bioinformatic strategies ( 77 ), although most attention has been dedicated to the effects of metformin a biguanide antidiabetic drug. In particular, it was shown that metformin is a powerful CLIC1 inhibitor in GSCs ( 78 ), and its repositioning as GBM drug could have a significant impact for the treatment of these patients.…”
Section: Development Of Pharmacological Tools To Target Clic1 Activitmentioning
confidence: 99%
“…This is especially true if the studied drug has already proven good safety and tolerability profile in humans ( 76 ). Interestingly, a CLIC1 inhibitory activity was reported in some Chinese traditional medicine molecules, identified by bioinformatic strategies ( 77 ), although most attention has been dedicated to the effects of metformin a biguanide antidiabetic drug. In particular, it was shown that metformin is a powerful CLIC1 inhibitor in GSCs ( 78 ), and its repositioning as GBM drug could have a significant impact for the treatment of these patients.…”
Section: Development Of Pharmacological Tools To Target Clic1 Activitmentioning
confidence: 99%
“…A potential drawback of molecular docking is doubt about its ability to predict weakly-binding fragment geometries with high fidelity. While docking has identified potent ligands from libraries of lead-like molecules (250 to 350 amu) (40)(41)(42)(43)(44)(45)(46), such molecules offer more functional group handles for protein matching than do most fragments (150 to 250 amu), and docking is thought to struggle with the smaller, less complex, and geometrically more promiscuous fragments (47,48). Thus, the pragmatism of this approach has been uncertain (49,50).…”
Section: Introductionmentioning
confidence: 99%
“…Then, 1 ns equilibration and 5 ns production phase MD simulations were carried out at 315 K to check the stability of docked complexes 21 . The analysis of MD simulations was performed using VMD software 22 . The frames of the production trajectories were aligned relative to the center‐of‐mass coordinates and the root‐mean‐square deviation (RMSD) was calculated with the initial equilibrated structures as the reference.…”
Section: Methodsmentioning
confidence: 99%